CL-oriented approaches to teaching phrasal verbs. A report on EFL classroom-based research: A report on EFL classroom-based research - Martín-Gilete, Marta (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
This article presents some ongoing work that is part of a project on classroom-based research into CL-oriented activities for teaching/learning phrasal verbs in English. Framed in a three-month longitudinal study, this investigation reports on the design, implementation, and assessment of CL-oriented activities aiming at fostering awareness of the meaning of the particles IN/OUT and UP/DOWN with intermediate-level Spanish speakers of English (N=81). Results were described concerning two different methods used to measure students’ learning gains: feedback from the classroom and formal assessment. Findings are discussed regarding the mismatch between results reported from the classroom and quantitative results.